Fractional exhaled nitric oxide in a respiratory healthy general population through the lifespan - Christina Bal; Caspar Schiffers; Marie-Kathrin Breyer; Sylvia Hartl; Alvar Agusti; Ahmad Karimi; Wolfgang Pohl; Marco Idzko; Robab Breyer-Kohansal (Pulmonology)
Introduction and Objectives The fractional exhaled fraction of nitric oxide (FeNO) is used in clinical practice for asthma diagnosis, phenotyping, and therapeutic management. Therefore, accurate thresholds are crucial. The normal FeNO values over lifespan in a respiratory healthy population and the factors related to them remain unclear.Materials and Methods We determined FeNO levels in 2,251 respiratory healthy, non-atopic, and non-smoking participants from the Lung, hEart, sociAl, boDy (LEAD) cohort, a general population, observational cohort study of participants aged 6–82 years in Austria.Results The median FeNO value in the total study population was 13.0 [interquartile range: 9.0, 20.0] ppb, increases with age, and, except in young participants (<18 years: 9.0 [7.0, 12.0], ≥18 years: 15.0 [11.0, 22.0]), it was significantly lower in females versus males. Multiple regression analyses showed that body height and blood eosinophil counts were associated with higher FeNO levels, both in children/adolescents and adults. In children/adolescents, FeNO values were positively associated with total IgE levels, FEV1/FVC ratio, and urban living. In adults, FeNO was positively associated with age and negatively associated with the presence of cardiovascular and ischaemic vascular disease.Conclusions We identified the normal FeNO ranges within a respiratory healthy population at different age ranges and associated factors. Collectively, they serve as a reference to frame FeNO values in clinical practice.